1996
DOI: 10.1159/000217215
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant Effects of Low-Molecular-Weight Heparin following Thrombolytic Therapy in Acute Myocardial Infarction: A Dose-Finding Study

Abstract: The aim of the present study was to gain clinical experience with different dose levels of dalteparin, a low-molecular-weight heparin, following thrombolytic therapy in acute myocardial infarction. Compared to heparin, dalteparin has a longer half-life and a greater and highly predictable bioavailability, which would suggest dalteparin to be a convenient alternative. Twenty patients with ECG signs of acute transmural myocardial ischemia received streptokinase (1.5 million IU for 60 min) and were allocated to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…One dose finding study of LMWH treatment following thrombolysis in acute myocardial infarction presumed a target range of 0.6–1.0 anti-Xa U/ml (based on treatment with deep venous thrombosis) 23. In that study, daltaparin was used after thrombolysis with streptokinase; no major bleeding complications occurred; however, eight urogenital tract bleeding episodes and 17 venepuncture haematomas were described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One dose finding study of LMWH treatment following thrombolysis in acute myocardial infarction presumed a target range of 0.6–1.0 anti-Xa U/ml (based on treatment with deep venous thrombosis) 23. In that study, daltaparin was used after thrombolysis with streptokinase; no major bleeding complications occurred; however, eight urogenital tract bleeding episodes and 17 venepuncture haematomas were described.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies in patients with venous thromboembolism have shown that treatment with fixed dose subcutaneous LMWH is at least as effective and safe as treatment with dose adjusted intravenous unfractionated heparin 1819 LMWH has also been studied in unstable angina patients,20-22 and in one dose finding study following thrombolytic treatment 23…”
mentioning
confidence: 99%
“…96 Six studies examined LMWHs administered with thrombolytics. [97][98][99][100][101][102] Small dose-finding studies of dalteparin 97,98 and enoxaparin, 99 as well as randomized clinical trials of dalteparin 100 and enoxaparin, 101, 102 established safety. In the Biochemical Markers in Acute Coronary Syndromes (BIOMACS) II trial, 100 101 patients with myocardial infarction were randomized to receive either dalteparin 100 IU/kg subcutaneously or placebo just before SK, with a second dose of dalteparin 120 IU/kg given to all patients 12 hours after the first dose of either placebo or dalteparin.…”
Section: Adjunctive Therapy With Lmwhsmentioning
confidence: 99%
“…A total of 9 randomised clinical investigations that evaluated LMWHs in patients with acute myocardial infarction (AMI) were identified. Seven studies were not included for the following reasons: dose-finding studies (35,36) and investigations from which it was not possible to extract the clinical data (37)(38)(39). In addition, two other studies in which LMWH therapy was commenced after five days (40) or only a bolus dose of LMWH was administered (41), were not included.…”
Section: Acute Myocardial Infarctionmentioning
confidence: 99%